Pedagogic natural language processing resources for L2 education: Teachers’ perceptions and beliefs - Carlos Ordoñana-Guillamón; Pascual Pérez-Paredes; Pilar Aguado-Jiménez (Language Value)
Pedagogic natural language processing resources (P-NLPRs) are a group of online technologies that aid teaching practices and hold the potential to enable Data-Driven Learning approaches by providing teachers and students with linguistic information. This study explores the perspectives of L2 educators on the potential implementation of P-NLPRs in their teaching practices. A training module was designed to provide information on the potential applications of different P-NLPRs, from which quantitative data was gathered (n=77) at PRE- and POST-test. Additionally, individual interviews were carried out with some of the participants (n=4) five years later to assess long-term P-NLPR uptake. Results offer insight into educators’ perception towards adopting P-NLPRs for their language teaching. Their perspectives seem to differentiate three main groups: a) tools to help learners learn (i.e. online dictionaries, text-to-speech technologies); b) tools to help teachers teach (i.e. automatic summarization tools, lexical profilers), and c) tools to help expand linguistic knowledge (corpora, POS taggers, lemmatizers).